Síntese de 14-aril-14h-dibenzol[a,j]xantenos e 4-aril-3,4-di-hidrobenzo[f]cumarinas promovida pelo pentacloreto de nióbio, com potencial aplicação na preparação de corantes sensibilizadores para utilização em dispositivos de Grätzel - Bartolomeu, Aloisio de Andrade [UNESP] (2015)
The synthesis of dibenzoxanthenes and 4-aryl-3,4-dihydrocoumarins (neoflavonones) is of great interest in the field of organic chemistry because both moieties are found in natural and synthetic molecules which present applications as anti-inflammatory, antioxidant and antimicrobial agents. The one-pot reactions provide an interesting strategy for the preparation of these compounds since all the steps required can be carried out in the same reaction medium, without needing to separate the products at each step of the process. Therefore, these reactions reduce time, save energy and also allow us to obtain good structural complexity products. Hence, in this work, we investigate the use of niobium pentachloride as a Lewis acid in one-pot reactions to obtain 14-aryl-14H-dibenzo[a,j]xanthenes and 4-aryl-3,4-dihydro-benzo[f]coumarins, molecules with potential applications in the development of type D-Л-A dyes used in Grätzel Devices. The NbCI5 promotes the synthesis of the 14-aryl-14H-diabenzo[a,j]xanthene derivatives by a one-pot condensation reaction between 2-naphthol and aromatic aldehydes at room temperature, in acceptable reaction times and with excellent yields (70-98%). The use of NbCI5 in the multicomponent reaction between 2-naphthol, dimethyl malonate and aromatic aldehydes was also studied. This MCR proved to be a good synthetic route to obtain 14-aryl-14h-diabenzo{a,j]xanthene and 4-aryl-3,4-dyhydro-benzo[f]coumarin derivatives, with predominance of the 4-aryl-3,4-dihydro-benzo[f]coumarins (41-93%). The optical characterization of the derivatives of 14-aryl-14h-diabenzo[a,j]xanthene and 4-EYL-3,4-dihydro-benzo[f]coumarin revealed that these compounds have absorption bands in the ultraviolet region of the spectrum. For this reason, it is necessary to carry out structural changes in order to use them as dyes-sensitizers in Grätzel devices